2015
DOI: 10.1016/j.envpol.2015.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Concentration- and flux-based ozone dose–response relationships for five poplar clones grown in North China

Abstract: a b s t r a c tConcentration-and flux-based O 3 doseeresponse relationships were developed for poplars in China. Stomatal conductance (g s ) of five poplar clones was measured to parameterize a Jarvis-type multiplicative g s model. The maximum g s and other model parameters varied between clones. The strongest relationship between stomatal O 3 flux and total biomass was obtained when phytotoxic ozone dose (POD) was integrated using an uptake rate threshold of 7 nmol m À2 s À1 . The R 2 value was similar betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 73 publications
4
65
1
1
Order By: Relevance
“…Rooted cuttings of two hybrid poplar clones were cultivated into 20 L circular plastic pots on April 10, 2016. Based on our previous studies and Hu et al (2015), we selected widely-planted poplar clones '546' (P. deltoides cv. '55/56' × P. deltoides cv.…”
Section: Experimental Site and Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…Rooted cuttings of two hybrid poplar clones were cultivated into 20 L circular plastic pots on April 10, 2016. Based on our previous studies and Hu et al (2015), we selected widely-planted poplar clones '546' (P. deltoides cv. '55/56' × P. deltoides cv.…”
Section: Experimental Site and Plant Materialsmentioning
confidence: 99%
“…The relative biomass (RB) was calculated according to Hu et al (2015). Firstly, a linear regression between the actual biomass and the accumulated ozone exposure or the stomatal uptake was made for each poplar clone in order to obtain the y-intercept (i.e., the hypothetically maximum biomass at zero ozone exposure or uptake).…”
Section: Biomassmentioning
confidence: 99%
See 2 more Smart Citations
“…(2015) reported similar effects of O 3 on stomatal behavior of European and Japanese beech species, while Hu et al. (2015) found that poplar clones grown in China were comparable in sensitivity to European beech and birch. However, few such studies, providing a direct comparison of sensitivity, have yet been reported.…”
Section: Extrapolationmentioning
confidence: 99%